Słyszeć poprzez język. Pogłosy awangardy - Hejmej, Andrzej (Zagadnienia Rodzajów Literackich, 2019)
The paper addresses two main issues: the first relates to modern hearing and the phenomenon of a new understanding of sound in the world of modernity, the second — as a consequence — to the repercussions of the auditory experience in the works of representatives of the first avantgarde. The author, following various examples of avant-garde manifestations of “language-noise” (including the works of Filippo Tommaso Marinetti, Luigi Russolo, artists of Cabaret Voltaire in Zurich), points out that they reveal the compulsion to hear, to be in sound-noise. He highlights the special importance of early European avant-garde movements (such as Futurism and Dadaism) in the process of restoring the proper sound potential to language (and literature) and at the same time refers to the new understanding of literature in the context of the modern soundscape.